ANTIDEPRESSANT ACTIVITY OF THYMOQUINONE POSSIBLY THROUGH INVOLVEMENT OF CORTICOTROPIN RELEASING FACTOR - Jain, Harshita; Jain, Prateek; Ahirwar, Bharti; Ahirwar, Dheeraj (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Present study aimed to evaluate the antidepressant-like activity of thymoquinone (TQ) in unstressed and stressed condition and to explore the possible underlying mechanism for this activity. Methods: TQ (5, 10, and 20 mg/kg) and fluoxetine per se were administered to the unstressed and stressed mice; immobility periods were observed using forced swim test (FST) and tail suspension test (TST). Effect of corticotropin-releasing factor (CRF)-1 antagonist on antidepressant-like activity was also evaluated. The mechanism of action was also explored by measuring plasma corticosterone levels. Results: TQ (20 mg/kg) and fluoxetine per se significantly decreased immobility periods in stressed mice indicating significant antidepressant-like activity under stress. There was no significant effect on locomotor activity of the mice on treatment with TQ and fluoxetine per se. It significantly decreased plasma corticosterone level. Antalarmin (a CRF-1 receptor antagonist) significantly attenuated TQ induced the antidepressant-like effect in both FST and TST. Conclusion: TQ significantly produced antidepressant-like activity in mice possiâ€‘bly through inhibiting CRF activity and decreasing plasma corticosterone levels. Â